The Optimal Timing of Storage Additions to Solar Power Plants - Aidan Hughes; Jarred King; Eric Hittinger (Energies)
The addition of battery storage to solar plants enhances the ability of those plants to deliver electricity during high-value periods. However, the value proposition of storage improves over time due to falling battery costs and increasing volatility in electricity prices, making it unclear when storage adoption should occur. In this work, we consider a 100 MW solar plant constructed in the year 2022 and build a techno-economic model to determine the optimal system design and timing of storage additions in four locations (CAISO, NYISO, ERCOT, and PJM). We find that the optimal time to add storage is 5–10 years after solar plant construction and that the optimal storage quantity is much higher than the amount selected if storage is included during the initial plant construction. Additionally, the model suggests significant upscaling in inverter capacity, allowing storage to deliver electricity during brief high-price periods. We also consider the effects of temporary and permanent subsidies for batteries, showing that a long-term subsidy encourages economically optimal delays in storage adoption.